2002
DOI: 10.1081/jfp-120015491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Additives on Dough and Cookie Making Properties of Flour

Abstract: The study was carried out to see the effect of different recipe ingredients (shortening, sodium chloride, sugar, sodium bicarbonate and water) on dough and cookie properties. Dough properties were measured using mixograph and cookie fracture force was measured using Instron Universal Testing Machine. Dough and cookie properties were described using regression to fit a response surface analysis. The models computed had correlation coefficient (R 2 ) values ranging between 90.1-93.0%, regarded as appropriate. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Fu et al (1997) investigated that the additional fat really postponed the onset of viscous flow, while at the same time diminishing the elastic properties of the gluten. Singh et al (2002) found that increasing fat level decreases dough development time and peak height. This effect of fat might be because of their lubricating effect in cookie dough.…”
Section: Role Of Fats and Oils In Dough Rheologymentioning
confidence: 97%
“…Fu et al (1997) investigated that the additional fat really postponed the onset of viscous flow, while at the same time diminishing the elastic properties of the gluten. Singh et al (2002) found that increasing fat level decreases dough development time and peak height. This effect of fat might be because of their lubricating effect in cookie dough.…”
Section: Role Of Fats and Oils In Dough Rheologymentioning
confidence: 97%
“…The rate of dough flow, expansion and setting time after the dough expansion during baking regulates the final cookie spread factor and diameter. The amount of ingredients used in the cookie formulation and their interaction affect the dough viscosity and hence the rate of spread (Singh et al 2002;Hoseney and Rogers 1994). However, conflicting results have been reported by researchers regarding effects of ingredients on the quality of cookies.…”
Section: Introductionmentioning
confidence: 99%
“…Also, ammonium bicarbonate and water significantly affected all responses, except stress-strain ratio, quadratically. Singh et al [31] also observed that the change in water and sugar content in the formulation affected the fracture force of cookies. The overall effect of sugar was found significant (p < 0.05) on spread ratio and OAA, whereas composite fat had on hardness at 5% and on OAA at 1%.…”
Section: Rsm Predictions Of Optimum Conditions For Use Of Fat Replacementioning
confidence: 95%